Community-acquired pneumonia in hospitalized adults: long-term morbidities and their risk factors - Jin H. Han; J. Jackson Resser; Adrienne Baughman; Carlos G. Grijalva; Jakea Johnson; Karen F. Miller; Craig S. Roberts; Kelly D. Johnson; Thomas Weiss; Wesley H. Self; for the PNEUMO Study Investigators (BMC Infectious Diseases)
Abstract Background The long-term morbidity associated with community-acquired pneumonia (CAP) and the risk factors associated with this long-term morbidity are unclear. In adults hospitalized for CAP, we sought to quantify the impact of CAP on loss of function, cognitive impairment, loss of employment, and quality of life six months after hospitalization for CAP and identify risk factors for these adverse outcomes. Design This prospective cohort study is an analysis of the Pneumococcal Pneumonia Epidemiology, Urine serotyping, and Mental Outcomes (PNEUMO) study population conducted at an academic, quaternary care hospital. Patients aged ≥ 50 years old and hospitalized for CAP between 2018 and 2020 were included in this analysis. Risk factors, including demographics, pre-illness status, comorbidities, delirium at enrollment, and pneumococcal etiology, were considered. Follow-up was conducted by phone six months after hospitalization for CAP to assess basic and instrumental activities of daily living (ADL), cognition, employment, and quality of life. Proportional odds logistic regression was performed to evaluate the association between potential risk factors and long-term morbidity. Results Of the 296 patients included in this analysis, 12.8% lost the ability to perform at least 1 basic ADL, 22.8% lost the ability to perform at least 1 instrumental ADL, 41.6% met criteria for cognitive impairment, 58.7% had a loss of employment, and 23.6% had decreased quality of life at 6-months. Poorer pre-illness ability to perform instrumental ADLs and quality of life, lower education, female sex, former and current tobacco use, past history of dementia, and delirium were associated with worsening 6-month outcomes, with the exception of employment. Conclusions Adult patients hospitalized for CAP suffered from significant morbidity at 6 months after discharge. Strategies are needed to prevent or mitigate these adverse outcomes, especially among those at higher risk.